High incidence of venous thromboembolic events in anticoagulated severe COVID‐19 patients. (27th May 2020) - Llitjos, Jean‐François; Leclerc, Maxime; Chochois, Camille; Monsallier, Jean‐Michel; Ramakers, Michel; Auvray, Malika; Merouani, Karim
Abstract: Background: Coagulopathy is a common abnormality in patients with COVID‐19. However, the exact incidence of venous thromboembolic event is unknown in anticoagulated, severe COVID‐19 patients. Objectives: Systematic assessment of venous thromboembolism (VTE) using complete duplex ultrasound (CDU) in anticoagulated COVID‐19 patients. Patients and methods: We performed a retrospective study in 2 French intensive care units (ICU) where CDU is performed as a standard of care. A CDU from thigh to ankle at selected sites with Doppler waveforms and images was performed early during ICU stay in patients admitted with COVID‐19. Anticoagulation dose was left to the discretion of the treating physician based on the individual risk of thrombosis. Patients were classified as treated with prophylactic anticoagulation or therapeutic anticoagulation. Pulmonary embolism was systematically searched in patients with persistent hypoxemia or secondary deterioration. Results: From March 19 to April 11, 2020, 26 consecutive patients with severe COVID‐19 were screened for VTE. Eight patients (31%) were treated with prophylactic anticoagulation, whereas 18 patients (69%) were treated with therapeutic anticoagulation. The overall rate of VTE in patients was 69%. The proportion of VTE was significantly higher in patients treated with prophylactic anticoagulation when compared with the other group (100% vs 56%, respectively, P  = .03). Surprisingly, we found a high rate of thromboembolic events in COVID‐19 patients treated with therapeutic anticoagulation, with 56% of VTE and 6 pulmonary embolisms. Conclusion: Our results suggest considering both systematic screening of VTE and early therapeutic anticoagulation in severe ICU COVID‐19 patients.